Regeneración temprana de Chusquea tomentosa (Bambusoideae-Poaceae) en Talamanca, Costa Rica - Grau, Héctor Ricardo; Rivera-Ospina, David; Arías, María Laura; Utzinger, Dagmar; Salas, Ingrid; Hernández, Francisco; Caballero, Magaly; Monge, Rafael; Calderón, Jorge; Coghi, Rita; Ruiz, Ivonne; García, Fernando M.; et al. (Revista de Biología Tropical, 1996)
El documento contiene los siguientes tìtulos: Regeneración temprana de Chusquea tomentosa (Bambusoideae-Poaceae) en Talamanca, Costa Rica Microbiological quality of some powder spices of common use in Costa Rica Fine structure of the capsule of Cryptococcus neoformans(Cryptococcales: Cryptococcaceae) Inhibitory substance residues in unpasteurized and pasteurized milk in a tropical city Coral colony fragmentation by whitetip reef sharks at Coiba Island National Park, Panamá Nest density of Trigona spinipes (Hymenoptera Apidae) in cerrado vegetation of central Brazil Hábitos alimentarios de Bufo marinus(Anura Bufonidae)en Costa Rica A case of lapsus calami in Costa Rican scorpion nomenclature Reply to Montoya about the use of the name Chactas bonito